Geology and structure of the main central thrust zone of the annapurna range, central Nepal Himalayas - Kano, Takashi (Journal of Nepal Geological Society, 1982)
The present paper describes the geology, structure, tectonic history and petrographical feature of lithologic constituents of the region around (MCT) zone. The report area is lithologically divided into four geologic units; the Midland zone, the MCT zone, the himalayan gneiss zone and the Tibetan Tethys zone. The MCT zone is distinguished by the lower augen gneiss zone, (MCT-2) and the upper thrust fault (MCT-1). Three stages of deformations are recognized in the area: the first, the two sets of widespread foldings with striation-like forms, which are comparable to the southwards thrusting of MCT; and the third, latest upwards movement of the Higher Himalayas. Mode of occurrence and petrographical feature of augen gneisses suggest close genetical relations with the movements of MCT and/or the activity of younger turmaline granites.